PENGUKURAN TINGKAT KEPUASAN PENGGUNA E-LEARNING DENGAN PENERAPAN MODEL END USING COMPUTING SATISFACTION (EUCS) (Studi Kasus: Universitas Bina Darma dan STMIK MDP) - Marlindawati Marlindawati; Poppy Indriani (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2016)
Development of Internet technology raises many new applications, including education, known as electronic learning (E-learning). In E-learning there are some menu navigation, such as: course info, descriptions of meetings, upload files, activities, discussions, and others who are prepared for the academic community. The purpose of this study to determine the level of satisfaction of users of e-learning with model approaches satisfaction of the end user computer (End-User Computing Satisfaction Model), which consists of five factors: Content (Content), Accuracy (Accuracy), Form (Format), Ease users (Ease to Use), and Timeliness (Timeliness) as independent variables and satisfaction as the dependent variable. Population and Sample were taken MDP University and Universitas Bina Darma who have been utilizing the E-learning as a mediator of information between faculty and students. The research data using instruments such as questionnaires and processed using SPSS software version 20.0